2022
DOI: 10.3389/fcvm.2022.1011037
|View full text |Cite
|
Sign up to set email alerts
|

Combined atrial fibrillation ablation and left atrial appendage closure: Watchman vs. LAmbre devices

Abstract: BackgroundLeft atrial appendage closure (LAAC) combined with radiofrequency catheter ablation is an emerging one-stop hybrid procedure for non-valvular atrial fibrillation (AF). This study was performed to compare the efficacy and safety of the Watchman device vs. the LAmbre device for this combined procedure.MethodsTwo hundred and thirty two patients with AF who underwent the combined procedure were enrolled and divided into two subgroups depending on the device choice: the Watchman-combined group (n = 118) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The patients underwent either a one-stop procedure (combined CA and LAAC) or LAAC. Catheter ablation was performed as previously described ( Ke et al, 2022 ). Antral ring electrical isolation of the left and right pulmonary veins was performed in all patients, and additional linear ablation was individualized according to requirements for persistent forms of AF or for redo ablation procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The patients underwent either a one-stop procedure (combined CA and LAAC) or LAAC. Catheter ablation was performed as previously described ( Ke et al, 2022 ). Antral ring electrical isolation of the left and right pulmonary veins was performed in all patients, and additional linear ablation was individualized according to requirements for persistent forms of AF or for redo ablation procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Several small trials comparing LAmbre with Watchman and Amulet have suggested comparable efficacy and safety profiles, although trials with larger enrollments are needed. [23][24][25] LifeTech gained FDA approval in March 2022 for a pre-market randomized multicenter trial comparing the safety and efficacy of LAmbre against OAC. The trial is anticipated to enroll more than 3,000 patients, with more than 1,500 implantations.…”
Section: Lambrementioning
confidence: 99%
“…US FDA approval will be necessary before wide clinical application can be achieved. Nonetheless, limited clinical comparison studies appear to suggest that the LAmbre™, Amulet™, and Watchman™ 2.5 all have high implant success rates, low risk of periprocedural adverse events, and good clinical outcomes [76,[81][82][83].…”
Section: Lambre™mentioning
confidence: 99%